2020
DOI: 10.3390/catal10010085
|View full text |Cite
|
Sign up to set email alerts
|

Application of TiO2-Cu Composites in Photocatalytic Degradation Different Pollutants and Hydrogen Production

Abstract: In the present work, copper nanoparticles were deposited onto the surface of two different commercial titanias (Evonik Aeroxide P25 and Aldrich anatase). During the synthesis, the concentration of copper was systematically varied (0.5%, 1.0%, 1.5%, 5.0%, and 10 wt.%) to optimize the composite-composition. The photocatalytic activity was evaluated under UV-light, using methyl orange and Rhodamine B as model and ketoprofen as real pollutant. For the hydrogen production capacity, oxalic acid was used as the sacri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…As a powerful and inexhaustible renewable energy source, solar energy is considered as one of the best methods to mitigate these problems. It can be exploited and utilized for energy production (for example H 2 [ 3 , 4 , 5 , 6 ], hydrocarbon fuel [ 7 , 8 ] and electric energy [ 9 , 10 ] production) and removal of pollutants (such as CO 2 [ 11 , 12 , 13 , 14 , 15 ], organic contaminants in water [ 16 , 17 , 18 , 19 , 20 , 21 ] or air [ 22 , 23 , 24 , 25 , 26 ], emerging micropollutants [ 27 , 28 ]) by using photocatalytic, photovoltaic and other light-conversion technologies [ 29 , 30 ]. As one of the most promising light conversion technologies, photocatalytic technology only needs the appropriate semiconductor photocatalyst and solar energy as energy input.…”
Section: Introductionmentioning
confidence: 99%
“…As a powerful and inexhaustible renewable energy source, solar energy is considered as one of the best methods to mitigate these problems. It can be exploited and utilized for energy production (for example H 2 [ 3 , 4 , 5 , 6 ], hydrocarbon fuel [ 7 , 8 ] and electric energy [ 9 , 10 ] production) and removal of pollutants (such as CO 2 [ 11 , 12 , 13 , 14 , 15 ], organic contaminants in water [ 16 , 17 , 18 , 19 , 20 , 21 ] or air [ 22 , 23 , 24 , 25 , 26 ], emerging micropollutants [ 27 , 28 ]) by using photocatalytic, photovoltaic and other light-conversion technologies [ 29 , 30 ]. As one of the most promising light conversion technologies, photocatalytic technology only needs the appropriate semiconductor photocatalyst and solar energy as energy input.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of palladium [93], a "series-parallel" reaction network has been proposed for describing the water splitting reaction using the mesoporous Pd-TiO2 and ethanol as organic scavenger (Figure 5) [94]. The addition of earth-abundant metals has a positive effect, in particular in the case of Ni [95] and Cu [96,97]. A high activity in hydrogen evolution under visible light has been demonstrated also for solid solutions of cadmium and manganese sulfides, due to their valence and conduction band position tuning, and for composite photocatalysts, CdS-β-Mn3O4-MnOOH, due to the ternary heterojunction formation [98].…”
Section: Photocatalytic Methodsmentioning
confidence: 99%
“…Other studies mention that the crystalline phase of anatase occurs when heat treatment varies between 200 and 500 • C. It was said that the amount and physicochemical properties (high ionic radii and electronic status) of the doping metal can influence the rate of transformation of anatase to the rutile phase [24,25]. Such is the case of a study conducted by Hampel et al [25]; they observed that TiO 2 doped with 5 wt.% Cu ions, calcined at 450 • C, contained an anatase phase and a rutile phase fraction, which increased with increasing Cu concentration from 5 to 10 wt.%. In our case, the dopant concentration does not influence the anatase-rutile transition because the maximum theoretical concentration of doping ions in TiO 2 is less than 1 wt.%.…”
Section: Xrdmentioning
confidence: 99%